Modeling of the Fate and Agrochemical Movement Under Controlled Water Table Environment - M. Almdny, Abdul Hakim; S., Salim; Mohd Soom, Mohd Amin (Universiti Putra Malaysia Press, 2003)
The study was undertaken to investigate the effect of water table management practices on the environmental transport and fate of agrochemicals. A laboratory based study using disturbed sand soil columns was conducted to investigate the transport and fate of nitrate (NO~), a commonly used agricultural chemical, to the underground environment as effected by controlled water table depths. Three controlled water table depths set as 0.25m, 0.50m, and 0.75m from the surface and free drainage treatment (no controlled water table depth) were used. A simple statistical model based on mUltiple linear regression analysis was developed using experimental data to simulate reduction and transport of nitrate in soil columns under different water table depths. The regression model was developed from selected physical variables including water table depth from the surface, time, and saturated depth. An imperial equation was obtained from the experimental data with a correlation coefficient of R2 =0.83. The performance of this equation was tested using experimental data and it was found that the output from this equation is acceptable and satisfactory.According to the simulated and observed results, it was clearly shown that the water table depth affects the characteristics of transport nitrate. In addition significant reduction in nitrate concentration was achieved through different water table treatments. The results suggest it is possible to promote biological and chemical degradation to reduce nitrate transport by controlling water table depths.